Social Democratic Parties and the Working Class New Voting Patterns - Rennwald, Line (Challenges to Democracy in the 21st Century, 2020)
This open access book carefully explores the relationship between social democracy and its working-class electorate in Western Europe. Relying on different indicators, it demonstrates an important transformation in the class basis of social democracy. At the beginning of the twenty-first century, the working-class vote is strongly fragmented and social democratic parties face competition on multiple fronts for their core electorate - and not only from radical right parties. Starting from a reflection on 'working-class parties' and using a sophisticated class schema, the book paints a nuanced and diversified picture of the trajectory of social democracy that goes beyond a simple shift from working-class to middle-class parties. Following a detailed description, the book reviews possible explanations of workers' new voting patterns and emphasizes the crucial changes in parties' ideologies. It closes with a discussion on the role of the working class in social democracy's future electoral strategies.